Biaya dan Waktu Proyek Gedung Satnarkoba dengan Metode CPM dan Metode PERT - Sari, Deviana Miranda; Agustappraja, Hammam Rofiqi; Arif, Samsul; Hepiyanto, Rasio (Jurnal Talenta Sipil, 2025)
In a building construction project, of course, there are many methods used to schedule a job as well as the cost budget. The purpose of this research is to determine the results of time and cost analysis on the Satnarkoba Police Lamongan Building Construction project. This research uses Critical Path Method (CPM) and Project Evaluation and Review Technique (PERT) with the help of Ms Word 2010 application program to analyze cost and time management. From the results of the analysis, a Network Diagram was found in which there was a series of critical work. Cost analysis is obtained by processing RAB and AHSP data. From this data, the volume, coefficient and wages of workers are obtained as a reference for processing workers' wage data. Based on the results of the analysis found, the critical trajectory, namely with work codes A, E, D, C, G, J, K, N, AF, and AE on a project that lasts for 180 days, gets an acceleration result of 144 days, so the chances of the project can be completed within 144 + 36 = 180 days, with a probability of 4.02%. Based on the results obtained, the average level of probability is greater than 4.02%, this is included in the very high category. In terms of costs incurred from each development, it shows optimal cost efficiency.